Miscalculation of two-phase turbulent jet parameters while using one-liquid mathematical model - Yu.V. Zuev (Учёные записки Казанского университета: Серия Физико-математические науки, 2020)
Conditions for applying a simplified single-speed and one-temperature (one-liquid) mathematical model, which makes it possible to determine the mean mass speeds and temperatures of the heterogeneous mixture, to calculate the two-phase turbulent non-isothermal jet were defined. Numerical modeling with use of the developed multi-liquid mathematical model of the two-phase jet, in which the speed and temperature of particles differ from the speed and temperature of the gas phase, was carried out. The problem under consideration is extremely important, because two-phase jet parameters are needed to solve numerous applied tasks in various technical areas. These parameters can be accurately determined with the help of simple mathematical models. Based on the resulting calculations carried out with the developed multi-liquid mathematical model of the two-phase turbulent jet, criterial dependences for assessing the maximum error of the calculation of two-phase jet flow parameters while using the one-liquid model were obtained.